Pervaporation separation of isopropanol-water mixtures using chitosan based membranes - Mohd Nawawi, Mohd Ghazali; Tan, Soon Huat; Hassan, Hashim (Faculty of Chemical and Natural Resources Engineering, UTM, 2001)
Pervaporation is a method for separating miscible liquids, usually water and organic compounds, using a dense polymeric membrane. The present study investigates the pervaporation performance of homogenous chitosan membranes for separating water from aqueous isopropanol solution at various conditions. Homogenous chitosan membranes were prepared from the locally available shrimp shells through various chemical treatments. Firstly the dried shrimp shells were ground to produce chitin flakes with the average size of 2-6mm. The decalcification of the chitin produced via treatment with hydrochloric acid was carried out to remove the calcium content.The chitin obtain was subsequently treated in 50wt.% of sodium hydroxide aqueous solution to remove acetyl groups from chitin to produce chitosan. Homogenous chitosan membranes were prepared by dissolving preweighhed chitosan in acetic acid aqueous solution. The effects of operating parameters, including feed concentration, feed temperature and downstream pressure on the separating performance on the membrane were investigated. At 30C and 5mmHg downstream pressure, a permeation flux of 48.8 g/m2.hr and permeate water concentration of 92.6 wt% was achieved at a feed water content of 5 wt.%. The temperature dependence of the permeation rate was expressed by an Arrhenius-type relation and with increased of the downnstream pressure would led to a reduction in permeation flux.